Dearomative Ring Expansion of Polycyclic Arenes. Issue 36 (26th July 2022) - Piacentini, Paolo; Bingham, Tanner W.; Sarlah, David
Abstract: Benzocycloheptenes constitute a common structural motif embedded in many natural products and biologically active compounds. Herein, we report their concise preparation from non‐activated polycyclic arenes using a two‐step sequence involving dearomative [4+2]‐cycloaddition with arenophile in combination with palladium‐catalyzed cyclopropanation, followed by cycloreversion‐initiated ring expansion. The described strategy provides a working alternative to the Buchner reaction, which is limited to monocyclic arenes. Overall, this methylene‐insertion molecular editing approach enables rapid and direct conversion of simple (hetero)arenes into a range of substituted (aza)benzocycloheptatrienes, which can undergo a myriad of downstream functionalizations. Abstract : A missing link between dearomative cyclopropanation and ring expansion of polycyclic (hetero)arenes has been established by utilizing an arenophile‐based strategy. This two‐step protocol enables the direct conversion of aromatic compounds into (aza)benzocycloheptatrienes, which are important structural motifs in natural products and biologically active compounds.